ASSESSING SHARIA COMPLIANCE OF LATE PAYMENT CHARGES IN GOLD INSTALLMENT SCHEMES - Muhammad Aziz Zakiruddin; Tri Yolanda (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
The implementation of non-cash gold transactions in Islamic finance requires a careful balance between risk mitigation and adherence to Sharia principles. DSN-MUI Fatwa No. 77/DSN-MUI/V/2010 mandates that the selling price (thaman) in gold installments must remain fixed, yet operational realities often require mechanisms to handle default risks. This study evaluates the alignment of late payment charge practices at Pegadaian Syariah Bengkulu with prevailing Sharia regulations. Employing empirical legal research, data were collected through in-depth interviews and document analysis. The results indicate that Pegadaian Syariah applies a progressive penalty mechanism ranging from 1% to 4% depending on the duration of the delay. While this mechanism effectively functions as a deterrent (Ta’zir) against negligent customers aligned with the spirit of Fatwa No. 17/DSN-MUI/IX/2000 the progressive calculation based on time presents a compliance gap regarding the fixed price requirement in Fatwa No. 77/2010. The study suggests that to minimize ambiguity regarding the time value of money, harmonization is needed by transitioning the penalty structure from a progressive percentage to a fixed nominal administrative fee. This adjustment would ensure stronger adherence to Sharia standards while maintaining operational discipline. Abstrak Pelaksanaan transaksi emas tidak tunai dalam keuangan syariah menuntut keseimbangan yang cermat antara mitigasi risiko dan kepatuhan terhadap prinsip Syariah. Fatwa DSN-MUI No. 77/DSN-MUI/V/2010 menegaskan bahwa harga jual (thaman) dalam cicilan emas harus tetap, namun realitas operasional sering kali membutuhkan mekanisme untuk menangani risiko gagal bayar. Penelitian ini mengevaluasi keselarasan praktik biaya keterlambatan di Pegadaian Syariah Cabang Bengkulu dengan regulasi Syariah yang berlaku. Menggunakan metode penelitian hukum empiris, data dikumpulkan melalui wawancara mendalam dan analisis dokumen. Hasil penelitian menunjukkan bahwa Pegadaian Syariah menerapkan mekanisme denda progresif berkisar antara 1% hingga 4% bergantung pada durasi keterlambatan. Meskipun mekanisme ini efektif berfungsi sebagai sanksi (Ta’zir) bagi nasabah yang lalai selaras dengan semangat Fatwa No. 17/DSN-MUI/IX/2000 perhitungan progresif berbasis waktu menunjukkan adanya kesenjangan kepatuhan (compliance gap) terhadap ketentuan harga tetap dalam Fatwa No. 77/2010. Penelitian ini menyarankan perlunya harmonisasi dengan mengubah struktur denda dari persentase progresif menjadi biaya administrasi nominal tetap. Penyesuaian ini bertujuan untuk meminimalkan ambiguitas terkait time value of money serta memastikan kepatuhan syariah yang lebih kokoh tanpa mengurangi disiplin operasional.